2010
DOI: 10.1002/jbm.b.31714
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the suitability of highly cross‐linked and remelted materials for use in posterior stabilized knees

Abstract: Posterior stabilized (PS) knee designs are a popular choice for cruciate sacrificing knee arthroplasty procedures. The introduction of PS inserts fabricated from highly cross-linked and remelted Ultra High Molecular Weight Polyethylene (UHMWPE) has recently generated concern as these materials have been shown to possess reduced mechanical properties. This study investigated whether highly cross-linked and remelted UHMWPE material (referred to as XRP) can be expected to perform similarly to historical gamma-air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Delamination is related to high subsurface contact stresses in TKR . Elevated oxidation levels, a consequence of chain scission and free radical formation during irradiation of CPE, have been noted in the subsurface region and can contribute to delamination through local mechanical property change . Moreover, studies of clinically retrieved HXPE are showing evidence of slow but progressive in vivo oxidation which has been postulated to result from reactions between residual or newly created free radicals with oxygen in vivo , and alternatively by oxidation of in vivo absorbed lipids such as squalene and cholesterols (components of synovial fluids in the joint), which occurs via similar free radical‐based mechanism as polyethylene.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Delamination is related to high subsurface contact stresses in TKR . Elevated oxidation levels, a consequence of chain scission and free radical formation during irradiation of CPE, have been noted in the subsurface region and can contribute to delamination through local mechanical property change . Moreover, studies of clinically retrieved HXPE are showing evidence of slow but progressive in vivo oxidation which has been postulated to result from reactions between residual or newly created free radicals with oxygen in vivo , and alternatively by oxidation of in vivo absorbed lipids such as squalene and cholesterols (components of synovial fluids in the joint), which occurs via similar free radical‐based mechanism as polyethylene.…”
Section: Discussionsupporting
confidence: 88%
“…Remelted and annealed HXPE have shown reduced initial mechanical and fatigue properties compared to conventional UHMWPE (CPE), both of which may raise the incidence of tibial post fractures. In an in vitro post fatigue comparison of shelf‐aged CPE to 100 kGy HXPE, it was found that CPE was stronger . However, it has been shown that with appropriate design considerations, such as increasing the tibial post thickness, HXPE can perform as well as CPE articular surfaces in in vitro impingement loading conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of the change of toughness (the ability of the material to resist crack propagation) with oxidation was not possible for these antioxidant retrievals. However, toughness of all the UHMWPE materials represented by the retrievals in this study varied with irradiation dose . As the irradiation dose used to cross‐link these antioxidant materials was increased above a conventional sterilization dose, the toughness of the materials was decreased compared to conventional gamma‐inert sterilized polyethylene retrievals.…”
Section: Discussionmentioning
confidence: 83%
“…These fractured acetabular components, while not commonplace, are likely due to the adoption of a more flaw intolerant material in a design containing notches in highly stressed locations of the component. TKR failures have indicated cam post impingement, delamination, as well as fatigue and fracture of posts 56–61. The use of XLPE in TKR warrant caution as the tibial components are subjected to high cyclic contact stresses and can have stress concentration in their cam post designs.…”
Section: Discussionmentioning
confidence: 99%